Effects of Automatic Speech Recognition Technology on EFL Learners' Willingness to Communicate and Interactional Features - Jiang, Michael Yi-Chao; Jong, Morris Siu-Yung; Lau, Wilfred Wing-Fat; Chai, Ching-Sing; Wu, Na (Educational Technology ＆ Society, 2023)
This study examined the effects of using automatic speech recognition (ASR) technology on Chinese students' willingness to communicate (WTC) in oral English and the development trajectories of their interactional features in a flipped EFL context. One hundred sixty undergraduates from a Chinese university participated in the 14-week quasi-experiment. Both groups were taught in a flipped fashion. The treatment group was required to use the ASR technology for oral practice in their pre-class self-learning, while the control group conducted their self-learning without the ASR technology. The results found that the ASR-based oral practice led to a significant between-group difference in students' WTC with teacher and class and WTC with non-Chinese, showing that the ASR technology may contribute to improving the Chinese students' WTC in oral English. Conversely, except for the between-group effect on negotiation for meaning, there was no significant difference between the two groups on the other measures of interactional features. Moreover, none of the interactional features of the students in the treatment group changed significantly over time, indicating a limited role of the ASR technology on Chinese students' interactional features. Discussions were conducted regarding the contradictory effects of the ASR technology on WTC and peer interaction.